Cardiovascular magnetic resonance assessment of biventricular changes during vacuum bell correction of pectus excavatum - Monti, Lorenzo (J Thorac Dis, 2019)
BACKGROUND: Evidence of cardiac dysfunction in patients with pectus excavatum (PE) remains controversial. A growing number of studies report increased exercise tolerance following surgery. Nevertheless, many consider the correction of PE a cosmetic intervention, with post-operative changes ascribed to the concurrent growth of the young patient population. No studies have investigated non-invasively the immediate cardiac changes following relief of the deformity. The aim of this study was to assess cardiac function before and during temporary sternal elevation using the non-invasive vacuum bell (VB) device on young adults with PE. METHODS: Adult patients scheduled for surgical correction of PE underwent cardiac magnetic resonance imaging (CMRI) before and during the application of the VB. Steady-state free precession sequences were used for the evaluation of biventricular volume and function. Phase contrast sequences measured the aortic and pulmonary flow to calculate stroke index (SI). Scans were analyzed post hoc by the same investigator. A control group of healthy individuals was assessed in the same way. RESULTS: In total, 20 patients with PE (mean age 23±10 years) and 10 healthy individuals (mean age 25±6 years) underwent CMR before and during VB application. Before intervention, baseline cardiac volumes and function were similar between the groups, with patient-values in the low-to-normal range. Following VB application, PE patients revealed a 10% increase in biventricular SI. Furthermore, left ventricular end-diastolic volume index (LV EDVI) improved by 8% and right ventricular ejection fraction (RV EF) increased by 7%. These findings were not mirrored in the healthy individuals. No correlations were found between improved cardiac parameters and the baseline Haller index (HI) of PE patients. CONCLUSIONS: Non-invasive, momentary correction of PE is associated with an immediate improvement in SI, RV EF and LV EDVI, not observed in controls. The findings suggest that sternal depression in PE patients affects cardiac function.